Imam Al Ghazali dan Kontribusinya dalam Ilmu Jiwa - Hadi, Abdul (Program Studi Pendidikan Agama Islam Fakultas Agama Islam Universitas Islam As-Syafi'iyah, 2018)
This study aims to show Al Ghazali’s role in knowledge building of psychology and his theory in behaviors among the modern psychology. Al Ghazali was known of the most influential scholar in the culture of his era, especially in the field of psychology, philosophy, and Sufi. He was scholar who firstly declared the psychology is a science about human and named it as a science of interpersonal of human (muamalah), and he came with the Conditional Learning Theory many age before Pavlov, Russian Physiologic Scholar who acclaimed as the funding father of that theory.In compare the Al Ghazali’s behaviors theory with behaviors theory of modern psychology especially in behaviors ingredients has much similarity, but has hugedifferent in the source of some behaviors. He considered that heart (Al qalbu) not mind, with it various meaning as the source of some behaviors. His conclusion in this matter based on the Alqur’an and Assunnah guidences.Some Moslem Scholars in Islamic countries that used to wondered and took unselectively of western psychology should not ignore the treasure of knowledge and research produced by ancestor of them, cause it believed more related to Muslim character and behaviors. And the Muslim Scholar must remember that the truth is not merely belong to western psychology result of study and research but belong of human at large as well.